2016
DOI: 10.1016/j.cell.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Immunogens Direct Affinity Maturation toward HIV Neutralizing Antibodies

Abstract: SummaryInduction of broadly neutralizing antibodies (bnAbs) is a primary goal of HIV vaccine development. VRC01-class bnAbs are important vaccine leads because their precursor B cells targeted by an engineered priming immunogen are relatively common among humans. This priming immunogen has demonstrated the ability to initiate a bnAb response in animal models, but recall and maturation toward bnAb development has not been shown. Here, we report the development of boosting immunogens designed to guide the geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
298
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 239 publications
(315 citation statements)
references
References 69 publications
8
298
0
Order By: Relevance
“…Encouragingly, many parallel results are found between the mouse immunization models and human repertoire analysis; VH1-2 + naive B cells expressing a 5 aa L-CDR3 bind to eOD-GT8 (6, 13, 16). In additional, both in vivo mouse experiments and direct screening of human B cells found eOD-GT8-specific VH1-2 + HCs paired with LCs using V genes of known VRC01-class bnAbs (13) and L-CDR3 sequences showing selection for the QQYxx motif used by VRC01-class bnAbs (6, 11, 13). Although VRC01-class responding cells were rare in Kymab mice, PCIN63-subclass, VRC23-subclass, and N6-subclass B cells were all found in the Kymab model (13), similar to the subclasses identified in the naive human B cell repertoire.…”
Section: Discussionmentioning
confidence: 99%
“…Encouragingly, many parallel results are found between the mouse immunization models and human repertoire analysis; VH1-2 + naive B cells expressing a 5 aa L-CDR3 bind to eOD-GT8 (6, 13, 16). In additional, both in vivo mouse experiments and direct screening of human B cells found eOD-GT8-specific VH1-2 + HCs paired with LCs using V genes of known VRC01-class bnAbs (13) and L-CDR3 sequences showing selection for the QQYxx motif used by VRC01-class bnAbs (6, 11, 13). Although VRC01-class responding cells were rare in Kymab mice, PCIN63-subclass, VRC23-subclass, and N6-subclass B cells were all found in the Kymab model (13), similar to the subclasses identified in the naive human B cell repertoire.…”
Section: Discussionmentioning
confidence: 99%
“…103 Furthermore, administration of boosting immunogens (BG505 core-GT3 nanoparticle (NP) and BG505 SOSIP-GT3 trimer) drove the maturation of eOD-GT8 60-mer primed B cells toward VRC01-class bnAb and induced broad neutralization of near-native (N276A) viruses and weak neutralization of a fully native virus in VRC01 gH mice. 104 These data showed that B-cell lineage vaccine design has the potential to induce bnAb.…”
Section: Eliciting Broadly Neutralizing Antibodies Through Immunizationmentioning
confidence: 95%
“…However, apart from this example (77), it has been observed that, some early bnAb family members can only neutralize in the absence of specific glycan sites proximal to their epitopes. Such glycan shields are then tolerated by the related fully matured bnAbs (78,79). In summary, the large body of work on bnAb lineages to date has provided clues as to how breadth develops, and the significance of the glycan shield in restricting neutralization breadth.…”
Section: How Do Bnabs Develop During Infection?mentioning
confidence: 99%